AB0639 Influence of Infections on the Prognosis of Anca Associated Vasculitis (AAV). (9th June 2015) - Garcia Vives, E.; Ramentol, M.; Segarra, A.; Martínez-Valle, F.; Loureiro, J.; Agraz, I.; Solans-Laque, R.
Abstract : Background: Patients with AAV have a high risk of suffering serious infections. Understanding the risk factors associated with infections development is crucial to increase the life expectancy of these diseases. Objectives: To describe the incidence of infections in a wide cohort of patients with AAV, to investigate the risk associated factors, and the impact on the AAV evolution. Methods: Retrospective analysis of patients with AAV diagnosed and followed at the Internal Medicine Department of a tertiary Hospital over the last 20 years. Statistical analysis was performed with the SPSSv.19. Results: A total of 129 patients (46.5% male) were included, with a mean age of 54.6 y at diagnosis (17-86): 39% with GPA, 38% with MPA and 23% with EGPA. ANCA were positive in 111 (86%): 30% C-ANCA and 56% P-ANCA. The most common initial symptoms were toxic syndrome (77.5%), fever (66%), cough and dyspnoea, with lung infiltrates or nodules in 57% and alveolar haemorrhage in 19%; peripheral or central neurological involvement in 49%; ENT involvement in 47%; acute renal failure in 45%, reno-pulmonary syndrome in 15.5% and nephrotic syndrome in 9%; heart disease in 12%, and gastrointestinal affection in 8.5%. Anaemia (Hb 10g/dl) was present in 78% of cases. Almost all patients (99%) received oral glucocorticoids (GC), 64% IV GC, 43% oral cyclophosphamide (CF), 49% CF pulses, 25% Azathioprine, 12% Mycophenolate, 7% Methotrexate, and 8 patients biological therapy. Dialysis was required in 24 cases. TMP-SMX prophylaxis was given in 63% of cases. Eighty-nine patients had relapses during the follow-up, with a mean of 1.7 (0-9) per patient. Sixty-three (49%) patients presented a total of 246 bacterial infections: 41% bronchitis, 24% pneumonia, 11% urinary tract infections, 9% sepsis and 5% abdominal infections. Two patients suffered tuberculosis and 20, 22 opportunistic infections: 8 systemic mycoses, 3 CMV, 3 P jirovecci, 4 Clostridium difficile, 1 herpetic encephalitis, 2 leishmaniasis and 1 atypical mycobacteriosis. Bacterial (p=0.019) and opportunistic infections (p=0.003) were more frequent in patients with leukopenia, patients treated with high doses of GC, and cumulative doses of CF higher than 15gr. Thirty-four patients (26%) died in an average of 113.6 months (1 month-33years): 12%. in early stages (1-4m) due to refractory disease, and the remaining in later stages (21-402m) due to infection (42%), relapsed or terminal disease (30%), malignancies (9%) or ischemic events (6%). Severe renal failure at diagnosis (p=0.001), bacterial infections (p=0.013) (pneumonia: p=0.043; urinary infection: p=0.046; sepsis: p<0.001), age >65y at diagnosis (p=0.009) and PAM subtype (p=0.003) were significantly related to death. Conclusions: Uncontrolled vasculitis remains the leading cause of early mortality in AAV, while infections and treatment-related complications are the principal cause in later deaths. Reducing treatment-related toxicities and preventing infections is vital to improve the long-term prognosis. Our results confirm that leukopenia due to high cumulative doses of CF and GC is clearly related to infections development. Disclosure of Interest: None declared